Partnership transitions among Turkish immigrants and their descendants in Western Germany - Muserref Erdogan; Ayşe Abbasoğlu Özgören (Comparative Population Studies (CPoS), 2022)
Adaptation to host country behaviours encompasses both individual and social change, bringing about rising diversity issues in the host society and societal shifts in the country of origin. This study aims to detect whether Turkish immigrants and their descendants converge towards or diverge from the partnership practices of the native-born population in Western Germany. Specifically, transitions from (1) singlehood to the first partnership, (2) singlehood to the first marriage, (3) singlehood to the first cohabitation, (4) cohabitation to marriage and (5) marriage to divorce are investigated. Data from the Panel Analysis of Intimate Relationships and Family Dynamics (pairfam) survey for the period of 2008-2018 are used, applying Kaplan-Meier survival estimations and Cox proportional hazard models. This is the first study that includes natives, immigrants and their descendants simultaneously in an analysis of extensive partnership transitions covering practices of cohabitation, marriage and divorce and to investigate the proportionality assumption in Cox models. We formulate four research hypotheses based on the hypotheses of socialisation, adaptation and the cultural maintenance and segmented assimilation theory. Supporting our first hypothesis, our findings indicate a difference in partnership patterns between both first- and second-generation immigrants and natives, except for the finding that second-generation immigrants resemble the native pattern in their transition to the first union (including both cohabitation and marriage). Immigrants and their descendants tend to marry directly and have lower divorce hazard ratios than their native counterparts, while consensual unions are uncommon among Turkish immigrants. As suggested by our second hypothesis, the extent of the divergence varies across partnership transitions. Finally, our results provide support for our third hypothesis rather than the fourth in that partnership transition of Turkish immigrants' descendants more closely resembles that of first-generation immigrants compared to natives.
urn:nbn:de:bib-cpos-2022-13en0
Keywords: 300; Union formation; Divorce; Turkish Immigrants; Germany; Event history analysis